Cardiovascular risk assessment by Framingham score pre and post kidney transplant - Sousa, Marcos Vinicius de; Tenório, Nayara; Valle, Carla Feitosa do; Mazzali, Marilda (Brazilian Journal of Transplantation, 2016)
Cardiovascular mortality is the main cause for graft loss after a successful kidney transplant. Purpose: To analyze the risk for cardiovascular events by the Framinghan risk score, pre and 1-year after kidney transplant. Methods: Retrospective study analyzing the transplant Unit database of kidney transplants performed from January 2010 to January 2012. Inclusion criteria: age >18 years old, functioning graft 12 months post-transplant. Exclusion criteria: patient death or graft loss within the first year after transplant. Demographic and laboratory data were collected pre and 12 months post-transplant; the Framinghan risk score was calculated at those points. Pre-transplant echocardiogram was also analyzed. Results: From 230 kidney transplants performed during the studied period, 167 fulfilled the inclusion criteria. Sixty-three were excluded due to death or graft loss (n=29) or insufficient data for analysis. In the majority, the studied group was male (64.6%), mean age of 47.9+11.1 years old and recipients from deceased donor (97%). Echocardiogram showed a 67.5 +6.6% ejection fraction, left ventricular hypertrophy in 98%, with a low incidence of valvar calcification (2.5%). Framinghan score was similar pre and after transplant (16.4+14.9 vs. 18.3 +17.2, p=ns). However, analysis of isolated parameters showed a significant difference pre and after transplant. While pre-transplant risk factors were high blood pressure, lower HDL cholesterol, and active smoking, post-transplant risk factors were the occurrence of diabetes, higher total cholesterol that required anti-hypertensive therapy. Conclusion: the early after transplant results, recovery of renal function, hematocrit and nutritional levels in the body weight gain usually along with impaired metabolic parameters, mainly total cholesterol, triglyceryde and uric acid maintained a similar Framinghan risk score as pre-transplant levels.